UPAYA INDONESIA DALAM MENJADIKAN AMBON SEBAGAI KOTA MUSIK DUNIA MELALUI UNESCO - Pane, Violyta; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this research is to know the cultural diplomacy carried out by Indonesia in making Ambon City of Music. Indonesia sees that Ambon City has the potential to become a world music city. Indonesia is preparing Ambon City and carrying out various cultural diplomacy efforts to make Ambon City of Music. This study uses a constructivism perspective which believes that culture in this case music has an important role in creating world peace. This research is also guided by the theory of cultural diplomacy and the concept of soft power. The method used is a qualitative method with a descriptive model. This research data collection technique is through interviews and literature studies from several journals, books, documents and websites.            This research shows the results of the efforts made by Indonesia through UNESCO to make Ambon a world music city. The cultural diplomacy carried out by Indonesia is in the form of concerts or performances such as the Acapella International Music Show in The City of Music 2017 and the 2018 Amboina International Bamboo Music Festival, negotiations with world music cities such as Adeliade, Daegu, and Tongyeong, as well as holding conferences such as the Music Conference Indonesia 2018 and the 2019 Pacific Music Conference. The forms of diplomacy that have been carried out by Indonesia have succeeded in making Ambon the UNESCO version of the world's music city on the UCCN website on October 31, 2019. Keywords: Ambon, City of Music, Cultural Diplomacy, UNESCO